Pelatihan Pembuatan Wafer Pakan Komplit Berbasis Tongkol Jagung pada Kelompok Ternak Sipakainge Kota Parepare - Fitriani; Asikin, Nevyani; Yunarti, Yunarti; Jannah, Fathul; Denia, Ergi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to improve the knowledge and skills of the Sipakainge livestock group in utilizing corn cob waste, which has potential as animal feed. The method employed in this program was the society participatory approach, which included stages of counseling, training, and mentoring in the application of complete feed wafers for cattle. The evaluation instruments consisted of pre-tests and post-tests administered via Google Forms, and the results were analyzed quantitatively using the gain score (N-Gain) method. The outcomes of this program showed that farmers were able to optimize corn cob waste as a complete feed wafer, combined with Azolla pinnata as a protein source. The results indicated an increase in partners’ knowledge and skills, with two key assessment components: 85% for knowledge of complete feed wafer production and 90% for practical production skills. The implication of this activity is that the partner group now possesses a chopper and pressing machine, enabling them to independently produce complete feed wafers.